CUSTOMER EXPERIENCE DAN SERVICESCAPE PADA DESTINASI WISATA: ANALISIS 7P DAN DAMPAKNYA TERHADAP REVISIT INTENTION DI PANTAI BOSOWA - Nur Fadilah Ayu Sandira; Nulthazam Sarah (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The increasing competition among urban beach tourism destinations, which requires managers to create memorable experiences in order to enhance tourists’ revisit intention. Pantai Indah Bosowa, as one of the coastal destinations in Makassar City, offers a unique integration of natural scenery and commercial facilities that shape a distinctive recreational atmosphere. This research aims to analyze the role of customer experience and visual servicescape in influencing tourists’ revisit intention. A qualitative approach was employed through in-depth interviews and field observations. The findings reveal that emotional, sensory, and social experiences derived from sea views, sunset ambiance, cafés with live music, aesthetic photo spots, gazebos, and supporting facilities are the dominant factors encouraging revisit intention. Physical evidence and visual spatial configuration were identified as the most influential elements in shaping positive tourist experiences. The study concludes that the success of urban beach destinations is determined not merely by pricing and promotional strategies, but primarily by their ability to consistently create authentic, engaging, and memorable experiences for visitors.